Socio-Adaptive TPACK in Rural Schools: Teachers’ Experiences and Challenges - Rully Andi Yaksa; Muhammad Ferdiansyah; Zubaidah Zubaidah; Amir Syarifuddin (Ta'dib, 2026)
The integration of Technological, Pedagogical, and Content Knowledge (TPACK) has become a fundamental prerequisite for 21st-century education. However, existing literature remains predominantly focused on resource-rich urban environments, leaving a significant gap in understanding how TPACK is constructed within infrastructure-scarce rural contexts. This study aims to explore the lived experiences of teachers in Muaro Jambi Regency in negotiating technological constraints and to propose a contextualized adaptation model. Utilizing a qualitative Interpretative Phenomenological Analysis (IPA) approach, data were collected over a three-month period through semi-structured in-depth interviews with nine teachers from SMPN 1, SMPN 7, and SMPN 30 Muaro Jambi. Data collection continued until thematic saturation was achieved. The analysis focused on interpreting emergent themes related to teachers’ socio-adaptive TPACK practices within limited technological environments. The findings reveal that infrastructural limitations, rather than functioning solely as barriers, act as catalysts for the emergence of “Socio-Adaptive TPACK.” This model consists of three interconnected dimensions: (1) Technical Adaptation through low-tech optimization and teacher agency, (2) Pedagogical Adaptation through collaborative interaction with students, and (3) Collaborative Adaptation through intergenerational knowledge sharing and social cohesion among teachers. The study concludes that, in developing regions, TPACK should not be understood merely as an individual cognitive competence, but as a communal asset shaped through resilience, collaboration, and social capital. These findings imply that professional development programs should move beyond top-down technical training and instead foster sustainable communities of practice within rural schools.